EXPLORING CLUNGUP MANGROVE CONSERVATION THROUGH VIRTUAL FIELD TRIP MEDIA : TO IMPROVE STUDENTS CRITICAL THINKING CAPABILITY - Hidayatullah, Ilham Adenan; Sahrina, Alfi; Purwanto, Purwanto; Deffinika, Ifan (Universitas Muhammadiyah Mataram, 2025)
Abstrak: Penelitian ini dilatarbelakangi oleh permasalahan keterampilan berpikir kritis siswa yang tidak merata pada setiap siswa serta pembelajaran yang bersifat pasif pada materi konservasi. Penelitian ini bertujuan untuk mengembangkan media pembelajaran Virtual Field Trip (VFT) di Clungup Mangrove Conservation (CMC) yang mendukung pemahaman materi konservasi dan mengukur kemampuan berpikir kritis siswa. Penelitian ini menggunakan metode pengembangan 4D (Define, Design, Develop, Disseminate) dengan instrumen berupa wawancara, angket kebutuhan siswa, lembar validasi ahli, angket respons siswa, dan asesmen kemampuan berpikir kritis. Pengumpulan data dilakukan melalui analisis kebutuhan, validasi ahli, uji coba media, dan asesmen siswa dengan analisis data menggunakan skala likert. Hasil penelitian menunjukkan media VFT memiliki tingkat validitas sangat tinggi (93%), respons positif siswa sebesar 91.6%, skor kemampuan berpikir kritis rata-rata 81% (kategori tinggi) dan 94% siswa mencapai KKTP yang menunjukkan bahwa media ini membantu siswa dalam berbagai aspek berpikir kritis, seperti conveying simple explanations , forming basic skills, inferring, elaborating further explanations, dan organising tactics and strategies. Media VFT efektif dalam meningkatkan kemampuan berpikir kritis siswa, mendukung pemahaman konsep konservasi, dan menjadi alternatif inovatif dalam pembelajaran geografi. Abstract: This research is backgrounded by the problem of students' critical thinking skills that are uneven in each student and passive learning on conservation material. This research aims to develop Virtual Field Trip (VFT) learning media at Clungup Mangrove Conservation (CMC) that supports the understanding of conservation materials and measures students' critical thinking skills. This research uses the 4D development method (Define, Design, Develop, Disseminate) with instruments in the form of interviews, student needs questionnaires, expert validation sheets, student response questionnaires, and critical thinking skills assessments. Data collection was carried out through needs analysis, expert validation, media trials, and student assessments with data analysis using a Likert scale. The results showed that the VFT media had a very high level of validity (93%), a positive student response of 91.6%, an average critical thinking ability score of 81% (high category) and 94% of students achieved KKTP which indicated that this media helped students in various aspects of critical thinking, such as conveying simple explanations, forming basic skills, inferring, elaborating further explanations, and organising tactics and strategies. VFT media is effective in improving students' critical thinking skills, supporting the understanding of conservation concepts, and being an innovative alternative in geography learning.